Cooperative Education In Training Primary Class Teachers - Qumriniso Saydaliyevna Usmonova (Euro Asian Journal Publishing, 2024)
This article discusses the importance of cooperative learning in the preparation of future teachers. In particular, the concept of cooperative learning, its conditions, methods and tools are explained. Information is provided on the effectiveness of the use of the cooperative approach in the educational process
Keywords: cooperative; cooperation; training; education; science